OVERLAP STIMULATION OF PRIMARY AND SECONDARY B CELLS BY CROSS-REACTING DETERMINANTS - Klinman, N. R. (The Rockefeller University Press, 1973)
Experiments were carried out to test the validity of the hypothesis that postulated differences in the nature of the antigen receptors of primary and secondary B cells should be reflected in a greater specificity in primary B-cell stimulation (2). Enumeration of clonal precursors stimulated by either DNP-Hy, TNP-Hy, or a mixture of both antigens confirmed this hypothesis. Since the sum of primary B cells stimulated by DNP-Hy and TNP-Hy is approximately equal to the number stimulated by a mixture of both, overlap stimulation of primary B cells by these antigens could be considered negligible. In contrast, the stimulation of B cells from mice previously immunized with DNP-Hy showed extensive overlap of stimulation by DNP-Hy and TNP-Hy. Thus secondary B cells appear less fastidious in their affinity requirements for stimulation than primary B cells.